2018
DOI: 10.3906/sag-1707-125
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation, reliability, and validity of the Turkish version of the Cancer Fatigue Scale in patients with breast cancer

Abstract: Background/aim: The Cancer Fatigue Scale (CFS) was developed to evaluate the severity of fatigue in patients with breast cancer. The aim of this study is to translate and culturally adapt a Turkish version and investigate the validity and reliability of the CFS in Turkish patients with fatigue symptoms. Materials and methods: Eighty participants completed the Turkish version of the CFS for breast cancer and the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire ″Core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Higher total scores are indicative of higher levels of fatigue. Cronbach's α of this scale was .74 in Şahin et al’s (2018) validation study and .80 in this study.…”
Section: Methodssupporting
confidence: 60%
“…Higher total scores are indicative of higher levels of fatigue. Cronbach's α of this scale was .74 in Şahin et al’s (2018) validation study and .80 in this study.…”
Section: Methodssupporting
confidence: 60%
“…Only 23 studies (29.8%) provided information about criterion validity. Of these, 16 studies demonstrated positive (21%) criterion validity [21,27,33,38,[42][43][44][45][46][47][48][49][50][51][52] and just seven (9%) received an indeterminate rating [37,[53][54][55][56][57][58]. The remaining 54 (70%) studies did not provide information related to criterion validity.…”
Section: Section One: Overall Reporting Of Quality Assessment Criteria Of Crf Scalesmentioning
confidence: 99%
“…The CFS was translated into English but not tested psychometrically. Other translations include Chinese [25], Dutch [96], Turkish [52] and Greek [49] with good reliability (0.74-0.91). Based on the review findings, the CFS met the quality assessment criteria for content, construct and criterion validity as well as internal consistency.…”
Section: Section Two: Scale Characteristicsmentioning
confidence: 99%
“…9e11 Therefore, we decide to translate and validate the CFS because of its compactness, it is brief, it is easy to complete, 12 and besides it is a widely used instrument for the evaluation of cancer patients, classified as an excellent tool because it contains the main domains of the fatigue with a high reliable and excellent psychometric properties. 13 The CFS was developed in Japan, 14 and the validity and reliability has been tested in Iranian language, 15 Chinese, 12 German, 13 Greek, 16 Turkish, 17 and Persian. 18 The CFS consists of 15 items that assess fatigue in three domains: physical (seven items), affective (four items), and cognitive (four items).…”
Section: Introductionmentioning
confidence: 99%